The IMPLEMENTASI ASESMEN DIAGNOSTIK BERBASIS PROFIL PELAJAR PANCASILA PADA PEMBELAJARAN MATEMATIKA KELAS I SDN JOHO 01 SUKOHARJO - Zonna Aneka Surya, Firnie; Budiwan, Jauhan; Perdana, Ryzal; Hayati, Tri (Universitas Veteran Bangun Nusantara, 2024)
Education is a conscious and planned effort to make humans intelligent, skilled and have noble character. In educational practice in Indonesia, the government has launched the Independent Learning curriculum. The Independent Learning Curriculum aims to enable students to freely think, express, be creative, and access knowledge from various sources. In practice, the Independent Curriculum certainly cannot be separated from the learning and assessment process. The learning process and assessment are components that cannot be separated, if the learning process carried out is effective then it must be accompanied by an assessment that is able to facilitate students providing feedback on their strengths and weaknesses, so that students always experience development in a positive direction. Diagnostic assessment is a type of assessment that is very important to determine students' learning readiness, talents, interests and learning styles. Conclusions from this research First, implementing diagnostic assessments is very important in order to create learning that supports students. Second, the implementation of diagnostic assessments in class I mathematics learning is based on the Pancasila Student Profile so that its implementation can be in accordance with the nation's noble values. Third, the application of a diagnostic assessment based on the Pancasila Student Profile in class I mathematics learning is based on the learning theory of cognitive development by